Porifera: A Collaborative Tool to Support Systematic Literature Review and Systematic Mapping Study - Campos, Thiago Prado De; Damasceno, Eduardo Filgueiras; Valentim, Natasha Malveira Costa (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2022: Anais do XXXVI Simpósio Brasileiro de Engenharia de Software, 2022)
This paper presents Porifera, a collaborative tool to support Systematic Literature Review (SLR) and Systematic Mapping Study (SMS). The tool allows the creation of a project for a researchers team. The user defines the goal, the inclusion and exclusion criteria for selecting primary studies, the search string, and the digital libraries. Also, the tool imports publications and identifies duplicates. The selection process occurs with the individual application of criteria and resolution of disagreements. During the process, it is possible to observe the agreement and reliability of the researchers’ evaluations. Porifera works on a web platform and integrates external services for translation, reference citation, and linking publications’ files. Porifera’s use can improve review and selection processes, optimize time, and prevent errors while facilitating collaboration between researchers. A video about the tool is available at https://doi.org/10.5281/zenodo.6618315 .